Evaluation of the plantaris tendon: cadaver anatomy study with ultrasonographic and clinical correlation with tennis leg injury in 759 calves - Meyer, P.; Pesquer, L.; Boudahmane, S.; Poussange, N.; Demondion, X.; Dallaudière, B. (Skeletal radiology, 2022)
Objective The role of the plantaris muscle (PM) in the literature is not clear. The objectives of this study were as follows: (1) to study PM at the interface between the medial gastrocnemius and soleus muscle in a cadaveric series, (2) to compare anatomic results with ultrasound (US) in the general population, and (3) to identify the potential role of the PM in the genesis of tennis leg (TL) injury. Methods First, a cadaveric study was undertaken on six cadavers for descriptive and functional PM anatomy. Second, US evaluation was carried out for 670 calves in 335 subjects with no suspicion of a clinical tear in the thigh or calf muscle (group 1) and for 89 calves in 89 patients with tear symptoms (group 2). Study criteria were the presence or absence of PM tendon and the width measurement if present. Results The PM was present in all cadavers. Traction on the tendon showed its “limited” mobility due to the connective tissue adherence mentioned with no apparent gliding of PM, promoting TL injury. In US, 37 PM were absent (4.35%) in 23 subjects. PM tendon width measurement of group 1 and group 2 was, respectively, 3.93 + / − 1.10 mm and 3.96 + / − 1.10 mm. No statistically significant differences between width measurements were found according to side ( P = 0.74) or group ( P = 0.69). Significant differences in width were only found between genders in group 1 ( P = 0.014). Conclusion PM were absent in 4.35% population. The contraction of PM can promote tennis leg injury by increasing the shear forces at the level of the distal inter-aponeurotic region.